Mesenchymal stromal cells as treatment for acute respiratory distress syndrome. Case Reports following hematopoietic cell transplantation and a review - Sadeghi, Behnam; Ringdén, Olle; Gustafsson, Britt; Castegren, Markus (Frontiers in Immunology, 2022)
Acute respiratory distress syndrome (ARDS) is a life-threatening lung disease. It may occur during the pancytopenia phase following allogeneic hematopoietic cell transplantation (HCT). ARDS is rare following HCT. Mesenchymal stromal cells (MSCs) have strong anti-inflammatory effect and first home to the lung following intravenous infusion. MSCs are safe to infuse and have almost no side effects. During the Covid-19 pandemic many patients died from ARDS. Subsequently MSCs were evaluated as a therapy for Covid-19 induced ARDS. We report three patients, who were treated with MSCs for ARDS following HCT. Two were treated with MSCs derived from the bone marrow (BM). The third patient was treated with MSCs obtained from the placenta, so-called decidua stromal cells (DSCs). In the first patient, the pulmonary infiltrates cleared after infusion of BM-MSCs, but he died from multiorgan failure. The second patient treated with BM-MSCs died of aspergillus infection. The patient treated with DSCs had a dramatic response and survived. He is alive after 7 years with a Karnofsky score of 100%. We also reviewed experimental and clinical studies using MSCs or DSCs for ARDS. Several positive reports are using MSCs for sepsis and ARDS in experimental animals. In man, two prospective randomized placebo-controlled studies used adipose and BM-MSCs, respectively. No difference in outcome was seen compared to placebo. Some pilot studies used MSCs for Covid-19 ARDS. Positive results were achieved using umbilical cord and DSCs however, optimal source of MSCs remains to be elucidated using randomized trials.